2020
DOI: 10.13045/jar.2019.00311
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Complex Korean Medical Treatment with Acupotomy on Irritable Bowel Syndrome: A Case Report

Abstract: The effects of complex Korean medicine treatment including acupotomy, on irritable bowel syndrome (IBS) are reported in this case study. A 54-year-old woman with diarrheal symptoms that alternatively improved and worsened for many years and worsening abdominal pain visited the emergency room and was diagnosed with IBS; she was admitted for approximately 2 weeks at the Acupuncture and Moxibustion Department of National Medical Center (NMC). Numerical rating scale (NRS), irritable bowel syndrome-quality of life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Level of quality according to the 8 sub-items for case reports and the 10 sub-items for case series Evaluation according to the checklist criteria for each of the 8 sub-items revealed that Sub-item 2, "Was the patient's history Thigh circumference [26] Stroke sequelae 1 Post-stroke spasticity [43] Internal condition/disease 1 Irritable Bowel Syndrome [28] * n, number of case reports, case series by condition/disease. clearly described and presented as a timeline?"…”
Section: Level Of Quality Of the Case Reports And Case Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Level of quality according to the 8 sub-items for case reports and the 10 sub-items for case series Evaluation according to the checklist criteria for each of the 8 sub-items revealed that Sub-item 2, "Was the patient's history Thigh circumference [26] Stroke sequelae 1 Post-stroke spasticity [43] Internal condition/disease 1 Irritable Bowel Syndrome [28] * n, number of case reports, case series by condition/disease. clearly described and presented as a timeline?"…”
Section: Level Of Quality Of the Case Reports And Case Seriesmentioning
confidence: 99%
“…However, it has been reported recently in case reports where acupotomy has been performed, that it can be used to treat not only chronic pain conditions/diseases such as cervical pain, frozen shoulder, lumbar disc herniation, and arthritis, but it can also treat endocrine conditions/diseases such as obesity, congestive heart failure, and irritable bowel syndrome [19][20][21][22][23][24][25][26][27][28]. This indicates an increase in the utilization of acupotomy for various conditions/ diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Acupotomy has been used for musculoskeletal conditions such as osteoarthritis, trigger finger, and lumbar disc herniation [ 4 , 5 , 6 , 7 , 8 ]. Moreover, case reports demonstrate the application of acupotomy for diseases other than musculoskeletal conditions, such as irritable bowel syndrome, and the treatment of atrophic scars caused by skin adhesions [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%